2012
DOI: 10.1016/j.jtcvs.2012.07.063
|View full text |Cite
|
Sign up to set email alerts
|

Selective antegrade cerebral perfusion and mild (28°C-30°C) systemic hypothermic circulatory arrest for aortic arch replacement: Results from 1002 patients

Abstract: Current data suggest that ACP and mild systemic hypothermic circulatory arrest can be safely applied to complex aortic arch surgery even in a subgroup of patients with up to 90 minutes of ACP. Unilateral ACP offers at least equal brain and visceral organ protection as bilateral ACP and might be advantageous in that it reduces the incidence of embolism arising from surgical manipulation on the arch vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
114
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 24 publications
9
114
0
1
Order By: Relevance
“…Previous report showed that no significant difference was seen regarding the incidence of postoperative acute renal failure among three ACP duration groups. 5) The incidence rate of renal failure in duration of ACP ≥60 to 90 min was 8%. Incidence in our study was higher than that by Zierer et al 5) However, a case of AAD was excluded in their result.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous report showed that no significant difference was seen regarding the incidence of postoperative acute renal failure among three ACP duration groups. 5) The incidence rate of renal failure in duration of ACP ≥60 to 90 min was 8%. Incidence in our study was higher than that by Zierer et al 5) However, a case of AAD was excluded in their result.…”
Section: Discussionmentioning
confidence: 93%
“…5) The incidence rate of renal failure in duration of ACP ≥60 to 90 min was 8%. Incidence in our study was higher than that by Zierer et al 5) However, a case of AAD was excluded in their result. Other reported that ACP duration longer than 90 min was not associated with an increased risk of hospital death or permanent neurologic deficit during a surgery on thoracic aorta including AAD.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Mild hypothermia (28.1-34 ℃): some groups have used even warmer temperatures (30±2 ℃) with good results in both mortality, neurological deficits and organ failure (20,21).…”
Section: Hypothermiamentioning
confidence: 99%